Analisis Morfometrik Ternak Itik Manila (Cairina moschata) di Kecamatan Hamparan Perak Kabupaten Deli Serdang: Morfometric Analysis of Muscovy Duck (Cairina Moschata) at District of Hamparan Perak, Deli Serdang District - Andhika Putra; Tengku G. Pradana; Denny Alfachri (Fakultas Peternakan Universitas Papua, 2022)
Abstract Muscovy ducks are included in the genus Cairina (Cairina moschata) originating from Mexico, Central America and South America. In Indonesia, this type of duck is known as a duck (entok) or Muscovy duck (muscovy duck). The Muscovy duck belongs to poultry that has relatively shorter legs than its body; the fingers have swimming membranes; the beak is covered by a delicate, sensitive membrane; concave-shaped fur, thick and greasy. The Muscovy duck is a waterfowl that leads to meat as potential commodity that has to be cultivated. This study aims to determine the phenotypic diversity of the Muscovy duck based on morphometrics. The method used in this study was purposive random sampling with the provision that Muscovy ducks aged over 6 months with a total of 100 male and 100 female Muscovy ducks. The parameter measured in this study were beak length, neck length, body length, wing bone length, body weight, femur length, shank length and third finger bone length. The results indicate that the head includes the beak length of males 5.65 ± 0.35 cm and females 4.81 ± 0.31 cm. Male neck length 17.68±0.98 cm, and female 9.01±0.62 cm. Body parts include male body length of 25.86±0.86 cm, and female body length of 23.22±1.02 cm. The length of the wing bones of males is 27.50±1.24 cm, and that of females is 21.76±1.05 cm. Male body weight 3.45±0.20 kg, and female 1.99±0.28 kg. The legs include the length of the male thigh 8.72±0.44 cm, and the female 8.59±0.35 cm. male tarsometatarsus shank length 4.56±0.43 cm, and female 3.83±0.32 cm. The length of the third finger is 7.8±0.26 cm, and the female is 6.40±0.65 cm. The results showed that the morphometric size of the male Muscovy duck was longer than that of the female Muscovy duck due to its phylogenetic characteristics. Keywords: Muscovy Duck, Morphometric Abstrak Itik Muscovy termasuk dalam keluarga (genus) Cairina (Cairina moschata) berasal dari Meksiko, Amerika Tengah dan Amerika Selatan. Di Indonesia bebek ini dikenal dengan mentok (entok) atau itik Muscovy (muscovy duck) dan cukup berpotensi untuk dibudidayakan. Penelitian ini bertujuan untuk mengetahui keragaman fenotipik itik Muscovy berdasarkan morfometrik. Metode yang digunakan dalam penelitian ini adalah purposive random sampling dengan ketentuan itik Muscovy berusia diatas 6 bulan dengan jumlah data 100 ekor jantan dan 100 ekor betina itik Muscovy. Data yang diukur adalah panjang paruh, panjang leher, panjang badan, panjang tulang sayap, bobot badan, panjang tulang paha, panjang shank dan panjang tulang jari ketiga. Panjang paruh jantan 5,65±0,35 cm dan betina 4,81±0,31 cm. Panjang leher jantan 17,68±0,98 cm, dan betina 9,01±0,62 cm. Panjang badan jantan 25,86±0,86 cm, dan betina 23,22±1,02 cm. Panjang tulang sayap jantan 27,50±1,24 cm, dan betina 21,76±1,05 cm. Bobot badan jantan 3,45±0,20 kg, dan betina 1,99±0,28 kg. Panjang paha jantan 8,72±0,44 cm, dan betina 8,59±0,35 cm. Panjang shank tarsometatarsus jantan 4,56±0,43 cm, dan betina 3,83±0,32 cm. Panjang jari ketiga 7,8±0,26 cm, dan betina 6,40±0,65 cm. Kesimpulan: Ukuran morfometrik itik Muscovy jantan lebih panjang dari pada itik Muscovy betina karena sifat phylogenetik. Kata Kunci : Itik Muscovy, Morfometrik